The Development of Students' Creative Thinking Ability Using the Stem-Based Simulation Method about Single and Multiple Interest of Students of SMA N 3 Rantau Utara - Sri Dewi; Lily Rohanita (Budapest International Research and Critics University, 2022)
This research is a literature study on students' creative thinking skills. This study aims to analyze students' creative thinking skills using a stem-based simulation method regarding single and compound interests of North Rantau High School students. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study concluded that through the STEM teaching method, students were accustomed to working on questions with many correct answers or many strategies that could be used to solve problems. After being given the final task in the form of problems, the researchers arranged students' creative thinking patterns and analyzed the results of students' creative thinking by emphasizing the creative thinking aspect.